The effect of walking speed on spinal loads and trunk muscle forces using subject-specific musculoskeletal modeling: A database for clinical and modeling applications. - Jamshidian, Ali; Rouyin, Alireza; Nazemi, Hamed; Arjmand, Navid; El-Rich, Marwan (Journal of Orthopaedic Surgery & Research, 2025)
Background: Gait analysis of patients with spinal disorders at different walking speeds helps clinicians diagnose conditions and investigate treatment/rehabilitation effectiveness. A subject-specific database for trunk muscle forces and lumbar spine loads of healthy individuals during different walking speeds is therefore useful. Methods: Ten healthy participants walked at three speeds (slow, normal, and fast) while motion and force-plate data were collected. Force in trunk muscles and loads on the lumbar spine discs were estimated using subject-specific musculoskeletal simulations in OpenSim. Model predictions at different walking speeds were statistically compared. Results: The time-dependent subject-specific force in all major trunk muscles and compression/shear loads at all lumbar spine discs (T12-S1) were reported for all walking speeds. Significant differences were observed in the average of peak compression between the fast and both slow/normal walking speed conditions across all lumbar discs (p < 0.001). With the exception of the L4-S1 discs, significant differences in the average of peak anterior–posterior and medio-lateral shear loads were also found between the fast and both slow/normal walking speed conditions. Significant differences (p < 0.007) in the average of peak muscle forces were generally found between the fast and both slow/normal walking speed conditions. Conclusions: This study presents a normative, subject-specific database of lumbar loading and muscle forces during walking at multiple speeds. These data provide a useful reference for future research in spinal biomechanics and musculoskeletal modeling. Furthermore, the database may serve as a baseline for assessing altered gait patterns and spinal loads in individuals with spinal disorders, supporting future clinical applications.